2017
DOI: 10.1039/c7md00387k
|View full text |Cite
|
Sign up to set email alerts
|

New application of tiplaxtinin as an effective FtsZ-targeting chemotype for an antimicrobial study

Abstract: The filamenting temperature-sensitive mutant Z (FtsZ) protein is generally recognized as a promising antimicrobial drug target. In the present study, a small organic molecule (tiplaxtinin) was identified for the first time as an excellent cell division inhibitor by using a cell-based screening approach from a library with 250 compounds. Tiplaxtinin possesses potent antibacterial activity against Gram-positive pathogens. Both and results reveal that the compound is able to disrupt dynamic assembly of FtsZ and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The on−target activity of I26 on S. aureus FtsZ was thoroughly assessed through light scattering polymerization assays, GTPase assays, and TEM microscopy, revealing concentration−dependent enhancement of polymerization, a decrease in GTPase activity, and a significant increase in protofilament bundling in the presence of the compound. Moreover, I26 induces the mis−localization of GFP−tagged FtsZ in discrete and punctate foci, indicating the mis−formation of the Z−ring [53]. Docking simulations predicted the binding of I26 in the interdomain cleft, supported by hydrophobic interactions in the lipophilic channel and by a set of additional interactions with specific functional groups.…”
Section: Indoles (Tiplaxtinin)mentioning
confidence: 98%
See 1 more Smart Citation
“…The on−target activity of I26 on S. aureus FtsZ was thoroughly assessed through light scattering polymerization assays, GTPase assays, and TEM microscopy, revealing concentration−dependent enhancement of polymerization, a decrease in GTPase activity, and a significant increase in protofilament bundling in the presence of the compound. Moreover, I26 induces the mis−localization of GFP−tagged FtsZ in discrete and punctate foci, indicating the mis−formation of the Z−ring [53]. Docking simulations predicted the binding of I26 in the interdomain cleft, supported by hydrophobic interactions in the lipophilic channel and by a set of additional interactions with specific functional groups.…”
Section: Indoles (Tiplaxtinin)mentioning
confidence: 98%
“…Antibiotics 2020, 9,69 23 of 28 of GFP−tagged FtsZ in discrete and punctate foci, indicating the mis−formation of the Z−ring [53]. Docking simulations predicted the binding of I26 in the interdomain cleft, supported by hydrophobic interactions in the lipophilic channel and by a set of additional interactions with specific functional groups.…”
Section: Indoles (Tiplaxtinin)mentioning
confidence: 99%
“…Inspired by the preliminary evidence that suggests that NSAIDs (nonsteroidal anti-inflammatory drugs) possess antibacterial properties [68], Mathew and co-workers explored the in vitro anti-tubercular profile and MtbFtsZ activity of a series of compounds based on the scaffold of the NSAID sulindac (59, Figure 12 The indole oxoacetic derivative tiplaxtinin (62, Figure 12) is a human plasminogen activator inhibitor (PAI-1) indicated in the treatment of acute arterial thrombosis [70]. Recently, Sun and coworkers identified its promising profile as an antibacterial against Gram-positive strain and as a potent inhibitor of FtsZ [71]. Firstly, the authors studied the effects of a small library of approximately 250 compounds on B. subtilis morphology, which showed that tiplaxtinin (62) was able to cause the elongation of the rod-shaped microorganism.…”
Section: Quinazolinesmentioning
confidence: 99%
“…Finally, a The indole oxoacetic derivative tiplaxtinin (62, Figure 12) is a human plasminogen activator inhibitor (PAI-1) indicated in the treatment of acute arterial thrombosis [70]. Recently, Sun and co-workers identified its promising profile as an antibacterial against Gram-positive strain and as a potent inhibitor of FtsZ [71]. Firstly, the authors studied the effects of a small library of approximately 250 compounds on B. subtilis morphology, which showed that tiplaxtinin (62) was able to cause the elongation of the rod-shaped microorganism.…”
Section: Quinazolinesmentioning
confidence: 99%
“…Several characteristics render FtsZ a potential target for the development of new antibacterial agents: (i) it plays an essential role in bacterial cell division [45]; (ii) the structure and function of FtsZ are conserved across bacterial species [17,20]; (iii) it is absent in eukaryotes [69,70]; (iv) its structural and biological properties are well studied. So far, there are no drugs on the market targeting at FtsZ, but many researchers have made great efforts in studying FtsZ targeting compounds and their studies revealed that FtsZ inhibitors can lead to bacterial cell death via inhibition of cell division [71][72][73][74]. Most of these inhibitors will be discussed in the following sections.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%